1959
DOI: 10.1111/j.1469-8137.1959.tb05368.x
|View full text |Cite
|
Sign up to set email alerts
|

CYTOGHROME OXIDASE IN MYCORRHIZAL AND UNINFEGTED ROOTS OF FAGUS SYLVATICA

Abstract: Summary The effect of azide, cyanide, carbon monoxide and DNP upon the respiration of mycor‐rhizal roots of beech is stimulatory. The stimulations are shown to be the result of the reaction of the fungal sheath. Host tissue of mycorrhizas and of uninfected roots react in a more expected fashion and are inhibited by azide, cyanide and carbon monoxide. In spite of this the fungal sheath is shown to possess a succinic dehydrogenase‐cytochrome oxidase system inhibited by malonate, cyanide and azide. Host tissue, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1963
1963
1986
1986

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…As it is a component of the glycolytic sequence, the importance of this pathway for glucose catabolism in the fungus is brought into question, but there is considerable indirect evidence for its operation. Azide, cyanide and carbon monoxide, as well as dinitrophenol, bave a stimulatory effect on both oxygen uptake and carbon dioxide evolution by mycorrbizas, effects sbown to be largely due to the response of tbe fungal sbeatb (Harley et al, 1956;Harley and ap Rees, 1959). Such stimulation is accompanied by a rise in respiratory quotient, indicating a zymasis induced by the inbibitors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As it is a component of the glycolytic sequence, the importance of this pathway for glucose catabolism in the fungus is brought into question, but there is considerable indirect evidence for its operation. Azide, cyanide and carbon monoxide, as well as dinitrophenol, bave a stimulatory effect on both oxygen uptake and carbon dioxide evolution by mycorrbizas, effects sbown to be largely due to the response of tbe fungal sbeatb (Harley et al, 1956;Harley and ap Rees, 1959). Such stimulation is accompanied by a rise in respiratory quotient, indicating a zymasis induced by the inbibitors.…”
Section: Discussionmentioning
confidence: 89%
“…Such stimulation is accompanied by a rise in respiratory quotient, indicating a zymasis induced by the inbibitors. The increase of oxygen uptake occurs despite the presence of a functional succinic debydrogenase-cytochrome oxidase system (Harley and ap Rees, 1959). Also, tbe respiratory quotient in air, wbicb is close to unity, does not increase markedly until oxygen tension is reduced below 5 % (Harley, McCready and Brierley, 1953), but the relative contribution of fungus and host to this anaerobiosis was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Uninfected, that is, nonmycorrhizal, roots were obtained from beech saplings grown in sand culture essentially according to the method of Harley and ap Rees (1959).…”
Section: Methodsmentioning
confidence: 99%
“…l-r. and Neurospora crassa Shear and Dodge (Boulter and Hurst i960) and by mycorrhizal roots of Fagus sylvatica L. (Harley et al, 1956) must be through a system other than cytochronie oxidase but such evidence is not conclusive (Darby and Goddard, 1950b;Smith and Chance, 195S). Harley and ap Rees (1959) suggested that the fungal component of beech mycorrhizas contains a cytochrome system wbich, in the presence of inhibitors, diverts electron transfer through a non-phosphorylating by-pass around the inhibited oxidase. Such a system would be similar to cytochrome bj of aroids (Beevers, 1961;Hackett, 1963).…”
Section: Terminal Oxidasesmentioning
confidence: 99%